A distributed resource conservation multicast and spectrum allocation algorithm in cognitive wireless mesh networks. (1st January 2014) - Kuang, Zhufang; Wang, Guojun; Chen, Zhigang; Liu, Hui
A resource conservation wireless links weights computing function and computing algorithm (RCWC) are proposed. On this basis, a resource conservation joint multicast routing and spectrum allocation algorithm with QoS constraints in cognitive wireless mesh networks (RCDMSA) is proposed. Minimising the resource consumption of multicast tree is the objective of RCDMSA under the QoS constraints. Firstly, RCDMSA computes wireless links weights using RCWC algorithm. Secondly, RCDMSA constructs the resource conservation broadcast tree which contains source nodes and destination nodes using RCBT algorithm. Thirdly, the resource conservation multicast tree is pruned from the resource conservation broadcast tree. Simulation results show that RCDMSA algorithm can minimise the resource consumption of multicast tree, reduce overall network resource usage and increase network efficiency.